Pengaruh Geometri Basin Terhadap Aliran Vortex: Kajian pada Basin Conical, Conical Convex dan Silinder dengan CFD - Kurniawan, Iwan; Heri Siswanto; Yohanes, Yohanes; Romy, Romy; Amir Hamzah (SURYA TEKNIKA, 2024)
This study aims to evaluate the influence of basin geometry on the formation and characteristics of vortex flow using Computational Fluid Dynamics (CFD). Three types of basin geometries were investigated: cylindrical, conical, and conical convex. CFD simulations were conducted to observe the velocity distribution, and vortex flow patterns generated by each basin. The results indicate that the conical basin produces vortex flows with higher intensity compared to the cylindrical and conical convex basins. The conical basin demonstrated a more focused flow pattern and higher vortex concentration around the central axis, contributing to enhanced vortex formation efficiency. Although the cylindrical and conical convex basins also generated vortex flows, they exhibited a more dispersed velocity distribution and less stable vortices. These findings provide important insights for the design and optimization of vortex turbine systems, particularly in the context of renewable energy applications.